46,XX/46,XX,r(15) mosaiciam: report of a case. - Pfeiffer, R A (1977)
Mosaicism of cells with a normal karyotype or with a ring chromosome no. 15 was found in a girl with hypoplasia of the thumbs, club feet, mental retardation, and short stature, which seems to be a feature of this chromosomal aberration.